Determination of long-term creep properties for 316H steel using short-term tests on pre-strained material - Zhou, Haoliang; Mehmanparast, Ali; Nikbin, Kamran (Springer, 2021)
Determination of long-term creep rupture properties for 316H steel is both costly and time-consuming and given the level of scatter in the data would need substantial number of tests to be performed. The primary objective of this study is to estimate the long-term creep properties of cross-weld (XW) and as-received (AR) 316H stainless steel by performing accelerated tests on pre-compressed (PC) material. In this work, uniaxial creep rupture tests have been performed on XW specimens and the results have been used to establish a correlation with accelerated test results on the PC material. Moreover, tensile tests have been performed on XW specimens at room temperature and 550 °C to examine the pre-conditioning effects on the mechanical response of the material. Similar power-law creep properties have been found for the creep strain rate and rupture time behaviour of the XW and PC specimens. It also has been found that the creep ductility data points obtained from XW and PC specimens fall upon the estimated trend for the AR material at 550 °C when the data are correlated with the applied stress normalised by 0.2% proof stress. The results show that the long-term creep properties of the XW and AR material can be estimated in much shorter time scales simply by performing tests on the PC material state.
Keywords: Creep; Uniaxial creep; Cross-weld; 316H; Pre-compressed; Creep ductility